A Pengaruh Metode Pematahan Dormansi Dan Posisi Tanam Benih Terhadap Viabilitas Benih Salak (Salacca edulis Reinw) - I Made Leddy; Hayatiningsih Gubali; Nikmah Musa (Jurnal Penelitian Pertanian Terapan, 2024)
The hard and thick structure of snakefruit seeds makes it difficult for snakefruit seeds to germinate, therefore efforts are needed to break the dormancy of snakefruit seeds. The aim of the research was to determine the method of breaking dormancy and the appropriate seed planting position to increase the viability of snakefruit (Salacca edulis Reinw) seeds, which was carried out at the Green House of the Agriculture, Fisheries and Forestry Extension Center (BP3K). The research method uses a factorial pattern in a completely randomized design. The first factor is the dormancy breaking method which consists of 5 levels, namely control, atonic, gibberellin (GA3), 60oC hot water, and sanding. The second factor is the position of planting seeds which consists of 3 levels, namely upright, lying down and upside down. Data analysis was carried out using ANOVA with a DMRT further test at 5% level. The research results showed that the method of breaking dormancy had an effect on the viability of snakefruit seeds. A good method of breaking dormancy is with GA3. The position of seed planting influences the viability of snakefruit seeds. The positions for planting seeds that have a good effect are the upright and lying positions. There was an interaction between the method of breaking dormancy using GA3 and the planting position of the lying seeds on the viability of the snakefruit seeds.